Creating National Resilience through State Defence and Student Character at Gerakan Sekolah Belajar - Wiwik Handayani; Hariyo Sulistyantoro; Rizky Dermawan; Erna Tri Rusmala Ratnawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The crisis of national resilience in the younger generation has been widely discussed, marked by the formation of KOMCAD (Reserve Commander) for students. This action was formed to increase the value of state defence as the nation's next generation. Forming individual character takes a long time, so primary and secondary schools should immediately create a curriculum that includes state defence subjects. The problem is that there are still limited schools implementing the state defence subject curriculum, so this study aims to analyze the effect of state defence on national security and student character, as well as the effect of student character on national security in